SilverGear / Muhammad Daniel Rahmat ... [et al.] - Rahmat, Muhammad Daniel; Mohaini, Ali Imran; Mohd Isnin, Muhammad Shamsul Bahri; Herman, Aiman Amanda Syahirah; Daud, Shafwatunnur (2021)
SilverGear is one of the well-known companies in Malaysia that have developed a car-service workshop. The company is known for its relatively good service, which means that customers will not stop delivering their cars at the workshop. Originally established in 2001, the company is the first generation of the family, inspired by a famous company of the time, Mutiara Motor. The workshop was then successfully developed together by the second generation developing company. We can see how they manage work all through their workshop in the company's background section. Their strategy for developing the company is very appealing to customers that have 6 operational strategies: social media, radio, promotions, customer satisfaction, free food and drink and free t-shirt after 1 car service. Next is the analytical section of the company. We focus on SWOT, strengths, weaknesses, opportunities and threats. We can see, from the strength of their workshops, that they are very knowledgeable in advertising, customer service and their strong image.Competitors is one of their weaknesses, which is known across Johor and entire Malaysia as a larger company. The third section presents a summary of SilverGear's major problems, including the Covid-19 workshop, which had to close early, and which affected its profits. Furthermore, we focus on solving the SilverGear company problem, the pros and cons of every solution. In the last section we display images of the workshops in SilverGear, the products they often use, and clients very happy about their workshops. This assignment draws on data, interview and industry information.